Risk Factors for Chronic Cough in Young Children: A Cohort Study - Au-Yeung, Yin To; Chang, Anne B.; Grimwood, Keith; Lovie-Toon, Yolanda; Kaus, Michelle; Rablin, Sheree; Arnold, Dan; Roberts, Jack; Parfitt, Sarah; Anderson, Jennie; Toombs, Maree; O'Grady, Kerry-Ann F. (Frontiers in Pediatrics, 2020)
Background and Objective: Data on the predictors of chronic cough development in young children are scarce. Our primary objective was to examine the factors associated with young children developing a chronic cough, with a focus on childcare attendance. Methods: A secondary analysis of data collected in a prospective cohort study of children presenting to three emergency departments and three primary healthcare centers in southeast Queensland, Australia. Eligible children where those aged <6-years presenting with cough and without known underlying chronic lung disease other than asthma. Children were followed for 4 weeks to ascertain cough duration. The primary outcome was persistent cough at day-28. Logistic regression models were undertaken to identify independent predictors of chronic cough including sensitivity analyses that accounted for children with unknown cough status at day-28. Results: In 362 children, 95 (26.2%) were classified as having chronic cough. In models that included only children for whom cough status was known at day-28, symptom duration at enrolment, age <12 months [adjusted odds ratio (aOR) 4.5, 95% confidence interval (CI) 1.1, 18.7], gestational age (aOR 3.2, 95%CI 1.4, 7.9), underlying medical conditions (aOR 2.6, 95% CI 1.3, 5.5), a history of wheeze (aOR 2.6, 95% CI 1.4, 4.8) and childcare attendance (aOR 2.3, 95% CI 1.2, 4.4) were independent predictors of chronic cough. Amongst childcare attendees only, 64 (29.8%) had chronic cough at day-28. The strongest predictor of chronic cough amongst childcare attendees was continued attendance at childcare during their illness (aOR = 12.9, 95% CI 3.9, 43.3). Conclusion: Gestational age, underlying medical conditions, prior wheeze and childcare attendance are risk factors for chronic cough in young children. Parents/careers need to be aware of the risks associated with their child continuing to attend childcare whilst unwell and childcare centers should reinforce prevention measures in their facilities.